Ecological Impacts of Oil-Palm Plantation on Butterfly and Bird Species Diversity - Rozza Tri Kwatrina; Yanto Santosa; M Bismark; Nyoto Santoso (Jurnal Manajemen Hutan Tropika, 2018)
The expansion of oil-palm plantations in Indonesia is often blamed as the driving causes of deforestation and impacts on environmental changes including the destructed biodiversity. Our understanding regarding environmental impacts on biodiversity is still limited. We address this issue by examining the diversity of butterfly and bird species under two type habitat conditions in Central Borneo. We calculated the butterfly and bird species number, richness, evenness, similarity, and composition inside the established oil-plantation area comprising four large-scale plantations and seven smallholding plantations, as habitat after plantation establishment.  In comparison, we did so similarly inside secondary forest and shrubs, as habitat before oil-palm plantation establishment.  Our results revealed that the habitat after plantation establishment exhibited a higher number of butterfly and bird species than the habitat beforehand.  However, the richness, evenness, and similarity indices for the species revealed variations, which were affected by dominant species in two habitats.  The establishment of oil-palm plantation brought about significant impacts on the composition of species and affected the species similarities between two habitats. The oil-palm plantation landscape and reserved forest vegetation were essential in supporting diversity and ecological role of species on habitat condition after oil-palm plantation establishment.